Chinese investigative journalists' dreams : autonomy, agency, and voice - Svensson, Marina, 1961-; Sæther, Elin; Zhang, Zhi'an (Lexington Books, 2014)
This edited volume brings together scholars positioned in and outside of China, including former Chinese journalists, in a comprehensive and in-depth study of Chinese investigative journalists' dreams, work practices, and strategies. It is the first book that systematically addresses the roles and values of Chinese investigative journalists in different types of media, in the process addressing topics such as journalism education, different generations and sub-groups among investigative journalists, and gendered roles within investigative journalism. <span.